Feminist Encounters General Issue: with Theme of Gender and Embodiment in Narratives of Displacement - Sally R. Munt; Rose Richards (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2022)
Editorial: Feminist Encounters General Issue: with Theme of Gender and Embodiment in Narratives of Displacement